38/#924 Immunometabolic changes during weight loss induce tumor immunogenicity resulting in tumor regression. (4th December 2022) - Brennan, Martin; Dyck, Lydia; Prendeville, Hannah; Brennan, Donal; Lynch, Lydia
Abstract : Objectives: Endometrial cancer is the most common cancer of the female reproductive tract, and obesity is the greatest risk factor for endometrial cancer. We have recently found that in addition to enhancing tumor growth, obesity also impairs the anti-tumor immune response. Here, we investigated the effect of weight loss on the immune landscape of the tumor, during an interventional treatment for endometrial cancer in obesity patients. Methods: Metabolic surgery was performed on 12 patients deemed suitable (>18 years, BMI of 40 kg/m2 and diagnosis of grade 1 or 2 endometrial adenocarcinoma). Bulk-RNA sequencing of tumor biopsies was performed before and after surgery/weight loss. Formalin-fixed, paraffin-embedded endometrial tumor biopsies were processed for immunohistochemical staining of PD-L1, CD8 and CD3. Results: Of the 12 patients, all had significant weight loss 6 months post-surgery, with an average of 24% body fat loss. Complete pathological response was observed in 9 out of 12 patients, stable disease in 2 patients and progressive disease in one patient, at 6 months post-metabolic surgery. Tumor biopsy sequencing before and after weight loss shows a significant increase in HLA class I and class II genes. Immunostaining showed that weight loss increased CD8 T-cell infiltration and PD-L1 expression in endometrial tumors. Conclusions: Our results demonstrate the important role of weight loss in directing anti-tumor immunity in obese endometrial cancer patients by creating a more immunogenic tumor environment through upregulation of HLA.